Pengaruh Penggunaan ChatGPT terhadap Kemampuan Berpikir Kritis Mahasiswa Pendidikan Ekonomi - Yuniyarti Ahiri; Jafar Ahiri; Harjun; Muhammad Juwantho Lewa; Wahyu Muh. Syata (Indo Publishing, 2026)
This study analyzes the effect of ChatGPT usage on critical thinking skills of Economics Education students at FKIP Halu Oleo University. Quantitative method with 180 students from semesters 3-7 selected by proportionate stratified random sampling. Data were collected through questionnaires and critical thinking tests, analyzed using simple linear regression. Results showed ChatGPT usage had a significant negative effect on critical thinking skills (β=-0.994, p<0.001). The higher the intensity of ChatGPT usage, the lower students' critical thinking skills. Findings confirm cognitive offloading theory that AI dependence reduces analytical abilities. Structured usage guidelines and critical AI literacy are needed to prevent technology from hindering prospective economics teachers' critical thinking development.